2014
DOI: 10.7883/yoken.67.120
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of OXA-48 Carbapenemase-Producing Klebsiella pneumoniae ST101 from an Overseas Traveler Returning to Japan

Abstract: SUMMARY: OXA-48 carbapenemase-producing organisms have emerged rapidly worldwide and may be transmitted through patients who receive medical care abroad. To our knowledge, this is the second case of OXA-48-producing Klebsiella pneumoniae isolated from a patient who had returned to Japan after receiving treatment abroad.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…ST101 has been described as an emerging pandemic clone found in several countries e.g. Romania, 2012 [ 51 ]; Japan, 2012 [ 52 ]; Spain, 2012–2014 [ 53 ]; Algeria, 2014–2015 [ 54 ]; and others [ 1 ]. The two ST101 strains from the same patient (blood and catheter) were closely related and showed a similar plasmid profile, except for the aac6’-lb gene which was not identified in the assembly for CFSAN044572.…”
Section: Discussionmentioning
confidence: 99%
“…ST101 has been described as an emerging pandemic clone found in several countries e.g. Romania, 2012 [ 51 ]; Japan, 2012 [ 52 ]; Spain, 2012–2014 [ 53 ]; Algeria, 2014–2015 [ 54 ]; and others [ 1 ]. The two ST101 strains from the same patient (blood and catheter) were closely related and showed a similar plasmid profile, except for the aac6’-lb gene which was not identified in the assembly for CFSAN044572.…”
Section: Discussionmentioning
confidence: 99%
“…Since 2003, the endemic spread of these bacteria has been reported in countries such as Turkey, Morocco, Libya, Egypt, Tunisia, and India ( Nordmann and Poirel, 2014 ; Figure 4 ). The sporadic spread has been reported in France ( Liapis et al, 2014 ; Semin-Pelletier et al, 2015 ), Spain ( Oteo et al, 2013b ; Pena et al, 2014 ), Italy ( Giani et al, 2013 , 2014 ), Belgium ( Cuzon et al, 2008 ; Huang et al, 2013 ), the Netherlands ( Kalpoe et al, 2011 ; Dautzenberg et al, 2014 ), the UK ( Dimou et al, 2012 ; Thomas et al, 2013 ), Germany ( Pfeifer et al, 2012 ; Kola et al, 2015 ), Switzerland ( Potron et al, 2012 ; Seiffert et al, 2014 ), Argentina ( Poirel et al, 2011c ; Lascols et al, 2013 ), Lebanon ( Beyrouthy et al, 2014 ), Israel ( Adler et al, 2013 , 2015 ), Kuwait ( Poirel et al, 2012a ; Zowawi et al, 2014 ), Saudi Arabia ( Shibl et al, 2013 ; Liu et al, 2015 ), and Japan ( Nagano et al, 2013 ; Hashimoto et al, 2014 ). The prevalence of OXA-48 carbapenemases among carbapenemase-producing K. pneumoniae in Spain and France was particularly high (74 and 78%, respectively; Robert et al, 2014 ; Palacios-Baena et al, 2016 ).…”
Section: The Epidemiology Genetic Context Treatment Options and Dementioning
confidence: 99%
“…The ST11 isolates carried various carbapenemases, including NDM-1, VIM-1, OXA-48, KPC-2, and OXA-245 ( Lascols et al, 2013 ; Oteo et al, 2013b , 2015 ). In addition, ST14, ST15, ST101, ST147, and ST405 harboring bla OXA-48-like have often been reported in many countries, such as the USA ( Lascols et al, 2013 ), Spain ( Oteo et al, 2013b , 2015 ; Ruiz-Garbajosa et al, 2013 ; Arana et al, 2015 ; Cubero et al, 2015 ), the Czech Republic ( Hrabak et al, 2015 ), Libya ( Lafeuille et al, 2013 ), India ( Lascols et al, 2013 ), Germany ( Gottig et al, 2015 ), Finland ( Osterblad et al, 2012 ), France ( Liapis et al, 2014 ), and Japan ( Hashimoto et al, 2014 ). Recent results from 83 hospitals in Spain showed that OXA-48 (71.5%) and VIM-1 (25.3%) were the most frequently detected carbapenemases, and the most prevalent sequence types were ST11 and ST405 for K. pneumoniae ( Oteo et al, 2015 ).…”
Section: The Epidemiology Genetic Context Treatment Options and Dementioning
confidence: 99%
“…Thus, it is likely that this patient acquired MDR A. baumannii during his stay in Brunei. Receiving medical care abroad has been suggested as a potential route of transmission of MDR organisms [16,17]. The sequence type of A. baumannii isolated in this study was ST208, which often carries bla OxA-23 and appears to be an emerging lineage mediating the spread of carbapenem resistance [18].…”
Section: Discussionmentioning
confidence: 77%